Microbiologically influenced corrosion: The gap in the field - Puentes-Cala, Edinson; Tapia-Perdomo, Valentina; Espinosa-Valbuena, Daniela; Reyes-Reyes, María; Quintero-Santander, Diego; Vasquez-Dallos, Silvia; Salazar, Henry; Santamaría-Galvis, Pedro; Silva-Rodríguez, Ramon; Castillo-Villamizar, Genis (Frontiers in Environmental Science, 2022)
Microorganisms have evolved to inhabit virtually all environments on the planet, from oceanic hot-seeps to pipelines transporting crude and refined hydrocarbons. Often microbial colonization of man-made structures results in the reduction of their service life requiring preemptive or corrective human intervention. Microbiologically Influenced Corrosion (MIC) is caused by a set of intricate bioelectrochemical interactions between a diverse group of microorganisms and metallic surfaces. The complexity of MIC microbiomes and their mechanisms as well as the logistics constraints of industrial facilities are factors to consider when choosing suitable analytical methods for MIC monitoring. These generally reflect only a partial view of the phenomenon and in consequence, might lead to ineffective mitigation measures. This paper acknowledges the discrepancies between the fieldwork for MIC monitoring and the currently available technological advancements. It also highlights the most pressing issues that operators have in the field in light of the diversity of the microbial key players present in corrosive microbiomes. Finally, it compiles and outlines a strategy for the integration of novel molecular approaches aiming for a practical and accurate assessment of the microbial threat.